SISTEM INFORMASI DATA PENDUDUK DESA KERTAPATI KECAMATAN PAGAR JATI KABUPATEN BENGKULU TENGAH - Dedy Agung Prabowo; Fernaldo Christofer Dofiyer (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2021)
Kertapati village is located in central Bengkulu with the population about 1500 people who are classified as the most dense in the district of pagar jati. The management of population data that is still manual only in the book records, the lack and completeness of the kertapati people data is very concerning, so that when the population data is quickly needed, and the invalid population data becomes a problem of delay in reporting to the next steps. Building an information system is done to fix the invalid population data and create systemized population data in kertapati village while making it easier for those who need the data of kertapati villagers. Creation of a system is set using PHP programming language (hypertext prepocessor). With this information system, computerized kertapati village population data and safe and useful data storage for both the village and related parties population data, reporting, searching and matching of population data becomes easier and faster